Increased Intragenic IGF2 Methylation is Associated with Repression of Insulator Activity and Elevated Expression in Serous Ovarian Carcinoma - Huang, Zhiqing; Murphy, Susan K. (Frontiers in Oncology, 2013)
Overexpression of insulin-like growth factor-II (IGF2) is a prominent characteristic of many epithelial ovarian malignancies. IGF2 imprinting and transcription are regulated in part through DNA methylation, which in turn regulates binding of the insulator protein, CTCF, within the IGF2/H19 imprint center. We have shown that IGF2 overexpression in ovarian cancer is associated with hypermethylation of CTCF binding sites within the IGF2/H19 imprint center. The aim of this study was to investigate the methylation and binding capacity of a novel putative CTCF binding motif located intragenic to IGF2 and determine how this relates to IGF2 expression. In 35 primary serous epithelial ovarian cancer specimens, methylation of two CpGs, including one within the core binding motif and another adjacent to this motif, was higher in the 18 cancers with elevated IGF2 expression versus 10 with low expression (avg. 68.2% vs. 38.5%; p<0.0001). We also found that the CpG site within the CTCF binding motif is hypermethylated in male gametes (>92%; avg. 93.2%; N=16). We confirmed binding of CTCF to this region in ovarian cancer cells, as well as the paralog of CTCF, BORIS, which is frequently overexpressed in cancers. The unmethylated CTCF binding motif has insulator activity in cells that express CTCF or BORIS, but not in cells that express both CTCF and BORIS. These intragenic CpG dinucleotides comprise a novel paternal germline imprint mark and are located in a binding motif for the insulator protein CTCF. Methylation of the CpG dinucleotides is positively correlated with IGF2 transcription, supporting that increased methylation represses insulator function. These combined results suggest that methylation and CTCF binding at this region play important roles in regulating the level of IGF2 transcription. Our data have revealed a novel epigenetic regulatory element within the IGF2/H19 imprinted domain that is highly relevant to aberrant IGF2 expression in ovarian malignancies.